Bracelet-Like Ni0.4Cu0.6O Microstructure Composed of Well-Aligned Nanoplatelets as a Superior Catalyst to the Hydrolysis of Ammonia Borane - Li, Xianfeng; Gui, Liucheng; Zou, Huahong (Frontiers in Chemistry, 2019)
The development of novel catalysts with both high catalytic activity and low cost toward the hydrolysis of ammonia borane is an important subject in the field of hydrogen energy. In this communications, nanostructured NixCu1-xO composites with different morphology have been synthesized and their catalytic activities in AB hydrolysis is studied. It’s found that bracelet-like nanoplatelets were obtained at x = 0.4 and exhibit highest catalytic performance with turnover frequency of 33.43 molhydrogen min-1 molcat-1, which much higher than those of most of CuNi-based catalysts in the literature. Pronounced synergistic effects between CuO and NiO in AB hydrolysis also have been observed. Due to the superior catalytic performance and cheapness, the prepared bracelet-like nanoplatelets Ni0.4Cu0.6O catalysts can be a strong catalyst candidate in AB hydrolysis.